Spiritual Leadership and Job Satisfaction: A Proposed Conceptual Framework - Yusof, Juhaizi Mohd (Information Management and Business Review, 2011)
The objective of this study is to propose a framework that relates spiritual leadership theories to job satisfaction in a multidimensional approach. The framework is designed based on the previous literatures. Spiritual leadership components that will be included in the study consist of vision, altruistic love, hope/faith, meaning, calling and membership. Job Descriptive Index (JDI) is adapted to measure job satisfaction. JDI provides five subscales that measure different facets of job satisfaction describing various aspects of the respondent’s work experiences such as the work itself, pay/promotion, supervision, and coworkers. This study also included turnover intention in the framework to measure job dissatisfaction. In this study, nine hypotheses will be proposed based on the conceptual framework outlined.